Effects of Spinal Anesthesia in Geriatric Hip Fracture: A Propensity-Matched Study. Issue 5 (May 2022) - Rodkey, Daniel L.; Pezzi, Alexandra; Hymes, Robert
Abstract : Objectives: To identify whether anesthesia type is associated with surgical outcomes in geriatric patients undergoing operative treatment for a hip fracture. Design: Retrospective database review of prospectively collected data. Patients: Patients included in the American College of Surgeons National Surgical Quality Improvement Program database. All included patients were 65–89 years of age and had a hip fracture treated with internal fixation, arthroplasty, or intramedullary device. Patients were excluded for open, pathologic, stress-related, or periprosthetic hip fractures. Intervention: Use of spinal anesthesia (SA) or general anesthesia (GA). Main Outcome Measurements: Complications, mortality, and discharge destination. Results: A total of 23, 649 cases met inclusion and exclusion criteria and were successfully matched using propensity score matching: 15, 766 GA and 7883 SA. The odds of sustaining a complication were 21% lower in the SA group compared with those in the GA group (odds ratio SA/GA 0.791; 95% confidence interval, 0.747–0.838). The 30-day mortality rate was not correlated with SA or GA choice. Patients who underwent SA were significantly more likely to be discharged to home (odds ratio SA/GA 1.65; 95% confidence interval, 1.531–1.773). Conclusions: No mortality difference exists between patients undergoing SA and those undergoing GA for hip fracture surgery. For patients undergoing hip fracture surgery with SA, there is lower 30-day complication profile and higher discharge to home rate compared with those undergoing GA. Both anesthesia modalities may be acceptable. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.